2014
DOI: 10.1007/s11655-014-1336-z
|View full text |Cite
|
Sign up to set email alerts
|

Kidney tubular-cell secretion of osteoblast growth factor is increased by kaempferol: A scientific basis for “The Kidney Controlling the Bone” theory of chinese medicine

Abstract: This lends strong support to the original idea that the Kidney has a significant influence over bone-formation, as suggested by some long-standing Chinese medical beliefs, kaempferol may also serve to stimulate kidney repair and indirectly stimulate bone formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The authors found that kaempferol increased cell growth, secretion of osteoblast growth factor and level of BMPR II in opossum kidney cells. Findings from this study implied that kaempferol stimulated kidney repair which indirectly stimulates bone formation 57…”
Section: In Vitro Studies and Mechanism Of Action Of Kaempferol As A mentioning
confidence: 59%
See 1 more Smart Citation
“…The authors found that kaempferol increased cell growth, secretion of osteoblast growth factor and level of BMPR II in opossum kidney cells. Findings from this study implied that kaempferol stimulated kidney repair which indirectly stimulates bone formation 57…”
Section: In Vitro Studies and Mechanism Of Action Of Kaempferol As A mentioning
confidence: 59%
“…Treatment with noggin (a BMP-2 antagonist) blocked BMP-2-induced ALP activity, phosphorylation of SMAD1/5/8 and p38, thus suggesting that BMP-2 signaling was implicated in the osteogenic action of 8-prenylkaempferol 56. Apart from the protecting action of BMP-2 produced in osteoblasts, bone morphogenetic protein receptor II (BMPR II) was identified in opossum kidney cells 57. The authors found that kaempferol increased cell growth, secretion of osteoblast growth factor and level of BMPR II in opossum kidney cells.…”
Section: In Vitro Studies and Mechanism Of Action Of Kaempferol As A mentioning
confidence: 99%